Early effects of kidney transplantation on the heart - A cardiac magnetic resonance multi-parametric study. (15th October 2019) - Hayer, Manvir K.; Radhakrishnan, Ashwin; Price, Anna M.; Baig, Shanat; Liu, Boyang; Ferro, Charles J.; Captur, Gabriella; Townend, Jonathan N.; Moon, James C.; Edwards, Nicola C.; Steeds, Richard P.
Abstract: Increased native myocardial T1 times in chronic kidney disease (CKD) may be due to diffuse interstitial myocardial fibrosis (DIF) or due to interstitial edema/inflammation. Concerns relating to nephrogenic systemic fibrosis with gadolinium-based contrast agents (GBCA) limit their use in end-stage kidney disease (ESKD) to measure extracellular volume (ECV) and characterise myocardial fibrosis. This study aimed to examine stability of myocardial T1 and T2 times before, and within 2 months after kidney transplantation; a time frame when volume status normalises but myocardial remodelling is unlikely to have occurred, and to compare these with ECV using GBCA after transplantation. Twenty-four patients with ESKD underwent serial cardiovascular magnetic resonance imaging, including T1 and T2 mapping. GBCA was administered on follow-up provided eGFR was >30 ml/min/1.73 m 2 . Eighteen age- and sex-matched controls were studied at one timepoint. ECV (ECV 28 ± 2% vs. 24 ± 2%, p = 0.001) and T2 times were higher in ESKD compared to controls. After transplantation, septal T1 times increased (MOLLI 985 ms ± 25 vs. 1002 ms ± 30, p = 0.014; ShMOLLI 974 ms ± 39 vs. 992 ms ± 33, p = 0.113), LV volumes reduced (LVEDvol indexed 79 ± 24 vs. 63 ± 20 ml/m 2, p = 0.005) but LV mass was unchanged (LV mass index 89 g/m 2 ± 38 to 83 g/m 2 ± 23, p = 0.141). T2 times did not change after transplantation. Both ECV and myocardial T1 times are elevated in ESKD, supporting the theory that elevated T1 times are due to DIF, although a contribution from myocardial edema cannot be fully excluded. The lack of any fall in T1 or T2 times after transplantation suggests that myocardial T1 times are a stable measure of DIF in CKD. Highlights: ECV is elevated in ESKD suggesting the elevated myocardial T1 times observed are indicative of diffuse interstitial fibrosis. The contribution of myocardial oedema towards elevated T1 times and ECV cannot be excluded in ESKD. Native T1 times is a stable and reproducible biomarker of fibrosis.